The behaviour of the elements Ni, Co, Cu, Pb, Zn, Au, Ag, Mo, Sn, W and U in the magmatic, hydrothermal, sedimentary and weathering environments - Anderson, J R (Rhodes University, Faculty of Science, Department of Geology, 1979)
In the last two decades much has been published on the behaviour of certain elements in the magmatic , hydrothermal, sedimentary and weathering environments , but the information is scattered throughout the literature . This situation prompted the present study on the elements Ni, Co, Cu, Pb , Zn , Au, Ag , Mo , Sn, W and U. The behaviour of the elements Ni, Cu, Pb , ZN, Au, Sn , W and U has been studied experimentally in some depth. Ag has been moderately studied, but there is very little information about Co and Mo. Studies on the complexes formed by the elements within the hydrothermal and aqueous environment are often inconclusive and controversial , but conclusions are drawn as to the more likely complexes formed . A genetic classification of ore deposits is used as a framework for the discussion . The source of the elements is regarded as being the mantle, and therefore discussion on other possible sources is beyond the scope of this dissertation. The crystal chemistry and geochemistry of the elements are presented and the essay concludes with a discussion on the elements within their depositional environments
Keywords: Elements; Environment; Ore deposits; Classification; Geochemistry; Crystal chemistry